The Cetina Figurine (Archaeologia Adriatica, 2008)
The article reports on a new find of a typologically unique prehistoric pottery figurine from Sinj plain, which in its general stylistic characteristics belongs to the large group of statuettes such as have been discovered to the present at numerous Neolithic sites in the broad region of the Balkans. Its surprising and extraordinary appearance in Dalmatia can be explained through the process of the Neolithization of the eastern Adriatic region, in which ethnic components from the interior most probably participated. Once more the archaeological importance of the area along the Cetina River for the study of the prehistoric period is emphasized.
Keywords: Neolithic art; Dalmatia; Cetina region; Sinj plain